CHRONIC WOUNDS - MICROBIOLOGY AND BIOFILM FORMATION - Mitrova Telenta, Julija; Panovski, Nikola; Labachevska Gjatovska, Liljana; Kostovski, Marko; Ahtarova, Biljana; Dimova, Maja; Zafirova, Ivana; Bogdanovski, Nenad; Dohcheva Karajovanov, Ivana; Simeonovski, Viktor (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2024)
Introduction: Chronic wounds are wounds that do not heal for more than 4 weeks. Among the most important causes of wound chronicity are wound infection, biofilm formation with microbial agents that are resistant to antimicrobial agents. Aim: To investigate microbial agents in chronic wounds, their potential to form biofilm. Material and methods: This was a prospective study involving 24 patients from the University Clinic for in Skopje. Microbiological swabs were taken from patients with chronic wounds on the lower extremities,and were analyzed at the Institute of Microbiology and Parasitology, Faculty of Medicine in Skopje. The biofilm formation potential in isolates was determined using the tissue culture plate (TCP) biofilm detection method. Results: In 17 patients, at least one microorganism was isolated from 23 wounds, a total of 36, and in 7 patients there was no positive isolate from 7 wounds. Eighteen wounds (60%) had an isolate with the potential to form a biofilm. The following microorganisms from the wound samples were recorded: 17 (47%) isolates of the genus Staphylococcus, 4 (11%) isolates each from the genera Proteusand Pseudomonas, 3 (8%) isolates each from Enterococcusand Escherichia, 2 (6%) isolates from Streptococcus, 1 (3%) each isolate from the genera Acinetobacter, Enterobacterand Candida albicans. Conclusion: In 60% of the isolates, a biofilm formation with different degrees was confirmed. A statistically significant association was found between the degree of wound healing and isolates with low potential for biofilm formation, as well as the type of isolate.
Keywords: chronic wounds; microbial agents; biofilm; microbial swab; TCP